(3TQM GddHGH aj Yde GdEYQGHs - (3CHhYHO Gddg TeS GdOjf eMeO Hf YKeGf Hf eMeO Hf CHj Ydj GdYQVj GdRhRfjs; (3eMeO Hf eMeO Hf CMeO, JGL GdOjf GdCSaQGjjfj,J (B684 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf LeYJ MhGTj ddEeGe GdCSaQGjjfj GdeYQha HGdaGVd s
(3BNQgG (B:s
(3adfJe GdcJGH MGeOjf ddg JYGdi GfbVi JCdja gPg GdMhGTj HeOjfI fjSGHhQ SfI SJ hKdGKjf hSHY eFI s
(3HGdeYgO fSNI CNQi GfXQgG aj GdLRA GdChd (B89 (3fMhs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddehVhYGJs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdfMhs